SISTEM INFORMASI GEOGRAFIS LOKASI BANK, ATM DAN MONEY CHANGER PROVINSI GORONTALO - Abdul Rifai Saputra Lakita; Arip Mulyanto; Mohamad Syafri Tuloli (Diffusion: Journal of Systems and Information Technology, 2021)
The number of tourists who come to Gorontalo Province always increases from 2016 to 2019, the tourists who come are not only local tourists but also foreign tourists. The increasing number of tourists who come is not directly proportional to the number and evenness of the locations of banks, ATMs and money changers because many tourist sites in Gorontalo Province are located in regencies. This study aims to build a system that can make it easier for local tourists and foreign tourists to find the location of banks, ATMs and money changers and have foreign language and social information features. This research can assist users in finding the closest location to the Bank, ATM and Money Changer and this research also uses the prototype method which includes the stages of communication, design, prototype formation, prototype evaluation, prototype repair and final production. The results of this study indicate the Geographical Information System of Bank Locations, ATMs and Money Changers can be used to find the location of the closest Bank, ATM and Money Changer to the user.